2018
DOI: 10.1556/066.2018.0007
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides and polyphenols in sea buckthorn leaf tea have synergistic impact on studied colonic strains in vitro and bacteria in vivo

Abstract: Present research on prebiotics focuses on either polysaccharides or polyphenols. This study compared the individual and combined impact of polysaccharide, quercetin, and gallic acid (GA) treatment on three human faecal strains. In vitro pure culturing and correlation analysis confi rmed that the growth of both benefi cial microbe B. longum subsp. longum (0.695, 0.205: R 2 , slope, respectively) and pathogenic C. perfringens (0.712, 0.085: R 2 , slope, respectively) increased due to polysaccharide treatment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Many studies had shown that H. rhamnoides L. extract and its components such as polyphenols, flavonoids, polysaccharides, and volatile oils had antibacterial effects, as shown in Table . H. rhamnoides L. had a broad antibacterial spectrum, and had certain inhibitory effects on Gram-positive bacteria, Gram-negative bacteria, and some anaerobic bacteria. In addition, H. rhamnoides L. polysaccharides and polyphenols had synergistic effects, which inhibited the number of Escherichia coli and Clostridium perfringens in the feces of mice, and increased the number of probiotic bifidobacteria, showing a certain role in regulating the intestinal flora …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies had shown that H. rhamnoides L. extract and its components such as polyphenols, flavonoids, polysaccharides, and volatile oils had antibacterial effects, as shown in Table . H. rhamnoides L. had a broad antibacterial spectrum, and had certain inhibitory effects on Gram-positive bacteria, Gram-negative bacteria, and some anaerobic bacteria. In addition, H. rhamnoides L. polysaccharides and polyphenols had synergistic effects, which inhibited the number of Escherichia coli and Clostridium perfringens in the feces of mice, and increased the number of probiotic bifidobacteria, showing a certain role in regulating the intestinal flora …”
Section: Resultsmentioning
confidence: 99%
“…In addition, H. rhamnoides L. polysacchar-ides and polyphenols had synergistic effects, which inhibited the number of Escherichia coli and Clostridium perf ringens in the feces of mice, and increased the number of probiotic bifidobacteria, showing a certain role in regulating the intestinal flora. 107 Quality Markers Based on Protobotanical Phylogeny. In China, there are 5 species and 8 subspecies of H. rhamnoides L..…”
Section: Nutritional Componentsmentioning
confidence: 99%
“…The cycle conditions were 30 s at 94 8C, followed by 40 cycles of 5 s at 94 8C and 30 s at 60 8C. The primers for 16S rRNA of Bifidobacterium and Escherichia coli were generated in our previous study (Du et al, 2018). Ten-fold serial dilutions of target stain plasmid were used for the generation of a standard curve.…”
Section: Enumeration Of the Target Bacteria By Real-time Pcrmentioning
confidence: 99%